Design synthesis : integrated product and manufacturing system design - Britton, Graeme Arthur; Torvinen, Seppo J. (Boca Raton, [Florida] : CRC Press, 2014)
'This textbook provides a conceptual framework and methodologies for integrating product design and manufacturing. The readers should be able to use the framework and methodologies provided to jointly optimize the design/re-design of new products and manufacturing systems to produce better quality products faster and cheaper. The textbook includes homework problems and numerous real life examples. An SM and PP Slides will go along with the book to enhance textbook adoptions'--
Includes bibliographical references and index.
Keywords: Production engineering -- Textbooks; Product design -- Textbooks